2022
DOI: 10.1002/cam4.4760
|View full text |Cite
|
Sign up to set email alerts
|

Soluble form of CTLA‐4 is a good predictor for tumor recurrence after radiofrequency ablation in hepatocellular carcinoma patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Elevated baseline sCTLA4 also correlated with a higher risk of biochemical recurrence and increased progression in prostate cancer patients after treatment with radical prostatectomy, radiotherapy or surveillance [235]. Finally, among patients with hepatocellular carcinoma and chronic hepatitis C, high baseline sCTLA4 correlated with earlier local recurrence and development of intrahepatic metastasis after treatment with radiofrequency ablation [126]. Collectively these studies demonstrate that elevated levels of sCTLA4 prior to therapy associate with poor outcomes in cancer patients treated with a variety of conventional therapies.…”
Section: Sctla4mentioning
confidence: 75%
See 1 more Smart Citation
“…Elevated baseline sCTLA4 also correlated with a higher risk of biochemical recurrence and increased progression in prostate cancer patients after treatment with radical prostatectomy, radiotherapy or surveillance [235]. Finally, among patients with hepatocellular carcinoma and chronic hepatitis C, high baseline sCTLA4 correlated with earlier local recurrence and development of intrahepatic metastasis after treatment with radiofrequency ablation [126]. Collectively these studies demonstrate that elevated levels of sCTLA4 prior to therapy associate with poor outcomes in cancer patients treated with a variety of conventional therapies.…”
Section: Sctla4mentioning
confidence: 75%
“…Only a few studies have reported lower levels of sCTLA4 in cancer patients (early breast cancer [66,67], nasopharyngeal carcinoma [65], and clear cell renal cell carcinoma [125]) than in healthy donors. A single study, in patients with hepatocellular carcinoma with chronic hepatitis C infection, found higher concentrations of sCTLA4 to correlate with a later TNM stage and a larger tumor size [126].…”
Section: Sctla4 Expression In Cancer Patient Plasma/serum and Associa...mentioning
confidence: 99%
“…sCTLA-4, like membrance-bound CTLA-4, can bind to the B7 ligands and interfere with their ligation to CD28, thereby inhibiting T-cell response (Gu et al, 2018). Several studies have supported this by showing that patients with colorectal cancer and hepatocellular carcinoma have high serum sCTLA-4 levels (Omura et al, 2020;Teng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…After ablation, assessing the risk of tumor recurrence and monitoring early recurrence are positive preventive strategies that facilitate further management as early as possible in patients. Many biological markers can be used to evaluate tumor recurrence after ablation, including serum markers (e.g., VEGF, 118 sCTLA-4, 119 and CXCL10 73 ) and molecular markers in surgical specimens (e.g., keratin 19 120 ). However, these markers remain to be translated into clinical guidelines.…”
Section: Strategies To Prevent and Treat Hcc Recurrence After Tamentioning
confidence: 99%